El espacio social y la génesis de las "clases" - Pierre Bourdieu (Estudios sobre las Culturas Contemporáneas)
An acute reflection and critical analysis of socially produced classification systems. The marxist concept of social classes, which tends to reduce the complex multi-dimensionality of society to the ´economic´ and to confuse scientific classifications systems with the reality under study, is questioned.